One book, two language varieties - Barreiro, A.; Rebelo-Arnold, I.; Batista, F.; Garcez, I.; Kuhn, T. (Computational Processing of the Portuguese Language .PROPOR 2020. Lecture notes in Computer Science, 2020)
This paper presents a comparative study of alignment pairs, either contrasting expressions or stylistic variants of the same expression in the European (EP) and the Brazilian (BP) varieties of Portuguese. The alignments were collected semi-automatically using the CLUE-Aligner tool, which allows to record all pairs of paraphrastic units resulting from the alignment task in a database. The corpus used was a children’s literature book Os livros que devoraram o meu pai (The Books that Devoured My Father) by the Portuguese author Afonso Cruz and the Brazilian adaptation of this book. The main goal of the work presented here is to gather equivalent phrasal expressions and different syntactic constructions, which convey the same meaning in EP and BP, and contribute to the optimisation of editorial processes compulsory in the adaptation of texts, but which are suitable for any type of editorial process. This study provides a scientific basis for future work in the area of editing, proofreading and converting text to and from any variety of Portuguese from a computational point of view, namely to be used in a paraphrasing system with a variety adaptation functionality, even in the case of a literary text. We contemplate “challenging” cases, from a literary point of view, looking for alternatives that do not tamper with the imagery richness of the original version .